Abrasivity measurement of brittle rock after thermal treatment - Wang, Lu (2023)
Estimations of cutting-tool wear and rock-breaking efficiency during underground excavation and geo-energy extraction rely mostly on Cerchar abrasivity index (CAI) tests. However, the measurement of rock abrasivity may not be accurate for highly cracked rock after extreme treatment conditions (e.g., high temperature and rapid cooling). Here we conduct CAI tests on granite specimens after thermal treatment with different combinations of heating temperature and cooling rate. The results show that the CAI value is mainly increased during the first few millimeters scratching distance and strongly influenced by the stylus indentation during the subsequent scratching distance. We examine the stylus and rock interaction based on P-wave velocity and acoustic emission and suggest evaluating the wear flat by reconstructing intact stylus profile. A scratching distance of 10 mm is appliable for highly cracked rock with an acceptable measurement error. We finally discuss the evolution of rock brittleness that fundamentally controls the stylus indentation.